Theoretical and Empirical Research in Islamic Economics - Tahir, Sayyid (2013)
This paper summarizes salient features of the existing thinking on fiscal and monetary policies in the Islamic economics literature. It outlines institutional framework for these policies from the Islamic economics perspective. The nature and role of government, in the light of the Shariʽah principles, are revisited. The general goals for macroeconomic policies are discussed along with separate goals for each of the two policies. The argument is capped with a look at practical considerations in the actual working of both the policies. The following are the main points in the paper. (1) Roles of both the policies shall be complementary in the context of the overall objectives at the state level. (2) Thrust of both policies would be different from that presently recognized. These conclusions are drawn in the context of the government’s role being limited to prudent governance and the society’s economic and distributional concerns being addressed as much as possible without adopting the budgetary channel.